2022
DOI: 10.1111/aas.14048
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of vital sign abnormalities; association to clinical complications in 500 postoperative patients

Abstract: Background: Patients undergoing major surgery are at risk of complications, so-called serious adverse events (SAE). Continuous monitoring may detect deteriorating patients by recording abnormal vital signs. We aimed to assess the association between abnormal vital signs inspired by Early Warning Score thresholds and subsequent SAEs in patients undergoing major abdominal surgery.Methods: Prospective observational cohort study continuously monitoring heart rate, respiratory rate, peripheral oxygen saturation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
5
21
0
Order By: Relevance
“…In case of missing values in other variables used in the calculation of sustained deviations, the last observation was carried forward or backwards for a maximum of 30 mins in each direction. This is similar to other works from our group 13,14 . After a device was stopped, measurements were not carried forward.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…In case of missing values in other variables used in the calculation of sustained deviations, the last observation was carried forward or backwards for a maximum of 30 mins in each direction. This is similar to other works from our group 13,14 . After a device was stopped, measurements were not carried forward.…”
Section: Methodssupporting
confidence: 78%
“…We performed a sample size calculation using the method from Happ et al 12 Using data from our previous study on postsurgical patients 13 where we found a median of 6 mins of cumulative SpO 2 < 85% postoperatively, based on the assumption that the median cumulative duration would be 1 min preoperatively. Using an 80% power and an alpha of 0.05, we calculated that we needed 33 observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusions can only be drawn for COVID-19 patients. For other patient populations, alternative vital signs and summary measures might be more informative [ 31 ]. Since the continuous monitoring system was not implemented alongside standard intermittent monitoring, we could not compare the performance of summary measures with care as usual.…”
Section: Discussionmentioning
confidence: 99%
“…The data were obtained at Rigshospitalet and Bispebjerg Hospital in Copenhagen, Denmark from February 2018 to August 2020. The Danish Data Protection Agency approved the study (2012-58-0004) and the trial registered at http://ClinicalTrials.gov (project: NCT03491137) [6].…”
Section: Datamentioning
confidence: 99%